Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1108/03055720810904826
|View full text |Cite
|
Sign up to set email alerts
|

Trapped in a net: network analysis for network governance

Abstract: PurposeEspecially at the regional level co‐operation is seen as a prerequisite for innovation and competitiveness. Hence, political interest in fostering knowledge intensive networks is high. New forms of governance and additional strategic intelligence for decision makers are requested. Thus potential of the social network analysis (SNA) is discussed as methodology providing the information needed for strategic management of innovation networks. The aim of this paper is to assess the impact as a regional gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…There are some practical implications for policy; our results suggest that there is no one-sizefits-all network governance and structure, which is consistent with the findings from other studies of networks (e.g. Ahuja, 2000;Grasenick et al, 2008). The institutional, cultural and economic settings can differ among regions, and policy makers formulating policy to promote network formation to improve firms' innovation performance should be aware that reproducing the network governance and structure from successful regions may not be appropriate for (all) other regions.…”
Section: Discussionsupporting
confidence: 90%
“…There are some practical implications for policy; our results suggest that there is no one-sizefits-all network governance and structure, which is consistent with the findings from other studies of networks (e.g. Ahuja, 2000;Grasenick et al, 2008). The institutional, cultural and economic settings can differ among regions, and policy makers formulating policy to promote network formation to improve firms' innovation performance should be aware that reproducing the network governance and structure from successful regions may not be appropriate for (all) other regions.…”
Section: Discussionsupporting
confidence: 90%
“…Despite many advantages that the strategic alliances off er there are also risks that must be considered (Grasenick et al, 2008). The risks of these business relationships should be defi ned alongside the benefi ts.…”
Section: Resultsmentioning
confidence: 99%
“…The UCINET social network software package (Borgatti et al, 2002) was then utilized. As this was a full population study, a sociogram of the entire CoP was then constructed which demonstrated each members' incoming and outgoing ties (Gluckler and Doreian, 2016;Brusco et al, 2011;Grasenick et al, 2008). The results were then aggregated across all members in the CoP, enabling the identification of four distinct positional categories -isolate, leaf, mesh and super-node.…”
Section: Data Collection and Analysismentioning
confidence: 99%